(untitled) (Ghana Journal of Science, Technology and Development, 2022)
This study was conducted in the savannah agroecological zone of Ghana to assess the different sheep management systems and identify potential stressors that compromise sheep productivity under these systems. A questionnaire and on-farm observations were used to obtain data from 176 farms on management system types, resources, husbandry practices and productivity. Four management systems were identified in the study area, namely extensive (41.5%), semi-intensive (38.1%), intensive (6.3%) and tethering (14.2%). Feeding systems used were free grazing/scavenging (24.43%), herded grazing (17.05%), zero-grazing/intensive feeding (6.25%), grazing plus supplementation (38.07%) and restricted grazing in the rainy season (14.2%). Most (87%) farmers under the extensive system did not house their sheep at all, but 88.1% of farmers using the semi-intensive system housed their sheep year round. Floor spacing per sheep was 1.06, 2.31, 2.17 and 1.47 sheep/m2 for the intensive, semi-intensive, extensive, and tethering, respectively. Preweaning mortality was significantly higher (40%) than post-weaning to yearling (34.9%) and adult mortality rates (14.3%) (ê“2 = 292, P <0.001). The extensive system has the highest (32.8%) mortality rate and the intensive system the least (14.9%) (ê“2 = 151, P <0.001). Reproductive indices (lambing percentage, age at first lambing, lambing intervals, and abortion rates) were all significantly influenced by the management system, with sheep managed under the semi-intensive and intensive systems performing better than sheep managed under the extensive system and tethering. Extensive management and tethering of sheep may expose DjallonkÃ© sheep to disease stress, chronic undernutrition, heat stress and walking stress compared to sheep under more intensive systems.